2013
DOI: 10.1108/17579861311303690
|View full text |Cite
|
Sign up to set email alerts
|

Determination of onset of plasticity (yielding) and comparison of local mechanical properties of friction stir welded aluminum alloys using the micro‐ and nano‐indentation techniques

Abstract: PurposeThe purpose of this paper is to determine if the nanoindentation technique is a reliable method and whether it can be used to measure the surface hardness (H) in friction stir welded aluminum alloys. In order to test the reliability of nanoindentation technique, nanohardness values for friction stir welded aluminum alloys were compared to microhardness values. Additionally, the onset of plasticity (yielding) is investigated.Design/methodology/approachNanoindentation experiments were performed for the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
2
3
0
Order By: Relevance
“…44 Rar et al 45 observed that the same material, when allowed to creep for a long time, produced a higher value of pile-up/sink-in, indicating a switch from an initial elastic sink-in to a plastic pile-up. 43 The findings of the present study reveal that creep time has no impact on the pile-up/sink-in of rate sensitive aluminium alloy (Fig. 10), in agreement with similar studies in the literature.…”
Section: Localised Plastic Deformation: Pile-up/sink-in Mechanismsupporting
confidence: 92%
See 2 more Smart Citations
“…44 Rar et al 45 observed that the same material, when allowed to creep for a long time, produced a higher value of pile-up/sink-in, indicating a switch from an initial elastic sink-in to a plastic pile-up. 43 The findings of the present study reveal that creep time has no impact on the pile-up/sink-in of rate sensitive aluminium alloy (Fig. 10), in agreement with similar studies in the literature.…”
Section: Localised Plastic Deformation: Pile-up/sink-in Mechanismsupporting
confidence: 92%
“…The contact area is influenced by the formation of pile-ups and sink-ins during the indentation process. 20,43 To accurately measure the indentation contact area, pile-ups/sink-ins should be appropriately accounted for. The presence of creep during nanoindentation has an effect on pile-up, which results in incorrect measurement of the material properties.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cheng and Cheng reported a 22% pile-up for a work hardening exponent [30]. This is consistent with the fact that when h c /h approaches 1 for small H/E*, deformation is intimately dominated by pile-up [31,32]. On the other hand when h c /h approaches 0 for large H/E* it corresponds to purely elastic deformation and is apparently dominated by sink-in in a manner prescribed by Hertzian contact mechanics.…”
Section: Creep Protocolsupporting
confidence: 65%
“…The micro-indentation hardness that predicted from nano-indentation by applying the Nix-Gao model are in good correlation with Vickers hardness measurements for AA 6082-T6. Specifically, as it is reported in the literature for the base metal, Vickers hardness is equal to 0.98 GPa and for the nugget zone, Vickers hardness is equal to 0.69 GPa (Koumoulos et al, 2011a). Also, parent material consists of elongated and with common orientation grains with average grain length ,120 mm and nugget zone consists of much smaller and equiaxed grains with average grain length ,13 mm.…”
Section: Resultsmentioning
confidence: 69%